MOLECULAR MARKING OF SUNFLOWER LINES WITH DIFFERENT ABILITY TO SUPPRESSION OF THE CYTOPLASMIC MALE STERILITY PHENOTYPE - Yu. I. Karabitsina; I. N. Anisimova; V. A. Gavrilova; N. V. Alpatieva; A. G. Pinaev; E. B. Kuznetsova; V. T. Rozhkova (Труды по прикладной ботанике, генетике и селекции)
Ninety five lines of sunflower genetic collection differing by their ability to suppress the CMS phenotype were molecularly marked with the use of 7 primer pairs. Using the STS marker orfH522, a sterile (PET1) cytoplasmon was identified in 79 lines, which confirmed indirectly the presence of fertility restoration genes in their genotypes. The majority of these lines also have a complex of molecular markers linked to the Rf1 gene. The HRG01, HRG02 and STS115 markers showed the best diagnostic value in revealing the Rf1 gene in the examined material. The data on allelic variation of the microsatellite loci ORS224, ORS511 and ORS799 were obtained for the first time.